Sociolinguistic Analysis of Verbal and Non-Verbal Language in Children with Physical Disabilities - Widia Febriani; Silvia Marni; Ricci Germarni Tatalia (Jurnal Bebasan, 2024)
This study aims to understand verbal and nonverbal language used in communication, particularly in the context of language disorders and difficulties among children with disabilities. Language, as a medium of communication, can be expressed both verbally and in writing, and plays a crucial role in conveying ideas. This research focuses on analyzing the spoken language of children with disabilities to identify linguistic disorders and changes in language within their social environment. The findings reveal four distinct uses of verbal language and three uses of nonverbal language among children with disabilities, which vary according to their situation, condition, and age. These results are expected to contribute to the field of Sociolinguistics by providing insights into the dominance of nonverbal language in communication and the forms of language disorders observed in children with disabilities, particularly in the case study of a child named Aisyah. The study also identifies the factors contributing to language difficulties when verbal and nonverbal communication do not align.